Humanitarian Interventions and Human Rights Outcome in Pakistan - Leghari, Benazir (American Journal of International Relations, 2024)
Purpose: The aim of the study was to assess the humanitarian interventions and human rights outcome in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Humanitarian interventions, characterized by actions taken by external actors to alleviate human suffering within a country, have been subject to extensive scrutiny regarding their effectiveness in promoting human rights outcomes. The study suggests that while interventions can mitigate immediate humanitarian crises by providing aid, protection, and sometimes military intervention to stop atrocities, their long-term impact on human rights outcomes is variable and often complex. Several factors contribute to the mixed results of humanitarian interventions. Firstly, the motivations behind interventions can vary widely, ranging from genuine concern for human rights to strategic geopolitical interests. This can influence the scope and duration of interventions, impacting their effectiveness in achieving sustainable human rights improvements. Implications to Theory, Practice and Policy: Responsibility to protect (R2P), just war theory and constructivism may be used to anchor future studies on assessing humanitarian interventions and human rights outcome in Pakistan. Prioritize the needs of affected populations, ensuring interventions are tailored to address their specific vulnerabilities and human rights violations. Enhance coordination and cooperation among humanitarian actors, state institutions, and local organizations to maximize the effectiveness of interventions.